Seismic performance of staircases in the 3D analysis of buildings - Omnia Hussien AboElwafa Ahmed; Ashraf Adel Shawky (Cairo : Omnia Hussien AboElwafa Ahmed, 2016)
Stairs play an important role as the escape way, and consider as source of safety building when earthquake happened. One of the reason of stairs failure during earthquake that designer was not consider the stairs in the 3D analysis model and not study effect of the stairs on behavior of building during earthquake
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Civil Engineering
Issued also as CD
Keywords: Ductility factor; Over-strength factor; Response modification factor